Welfare as Simple(x) Equity Equivalents - Loïc Berger; Johannes Emmerling (Fondazione Eni Enrico Mattei (FEEM), 2017)
Inequity plays a fundamental role in the evaluation of social welfare in many dimensions. We revisit the concept of inequity, whether across states of world (uncertainty), across individuals (inequality) and across generations (intergenerational equity), using a common framework generalizing the discounted expected utilitarianism approach. We propose a general measure of welfare as equity equivalents and develop the corresponding inequity index. We then allow for different degrees of inequity aversion across the three dimensions to span a simplex of possible inequity preferences and relate it to the recent literature on this topic. We show that the ordering of aggregation across the different dimensions matters for welfare evaluations and that many welfare-theoretical approaches developed in the literature may be seen as special cases of this general framework.
Keywords: D60; D63; D30; 330; Utilitarianism; Inequality; Inequity Aversion; Risk Aversion; Intertemporal Welfare; Discounting